2009
DOI: 10.1056/nejmoa0908535
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Influenza A (H1N1) Vaccine in Various Age Groups

Abstract: These data suggest that a single dose of 15 microg of hemagglutinin antigen without alum adjuvant induces a typically protective immune response in the majority of subjects between 12 and 60 years of age. Lesser immune responses were seen after a single dose of vaccine in younger and older subjects. (ClinicalTrials.gov number, NCT00975572).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
244
9
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(292 citation statements)
references
References 9 publications
34
244
9
5
Order By: Relevance
“…These data corroborate that, as reported in children under 12 years of age, 23 ESRD and dialysis patients require two doses for adequate protection.…”
Section: Discussionsupporting
confidence: 91%
“…These data corroborate that, as reported in children under 12 years of age, 23 ESRD and dialysis patients require two doses for adequate protection.…”
Section: Discussionsupporting
confidence: 91%
“…However, the sero-protection proportion among subjects (73%) was slightly lower than reported proportions in healthy adults (79-95%). 7,9,10 In particular, the proportion among patients >65-y-old (58%) was rather lower than the reported proportions in age-matched healthy adults (79-80%). 9,10 No serious adverse effects were observed and all reported adverse reactions were self-limited.…”
Section: Discussionmentioning
confidence: 60%
“…We found that the following [10][11][12] and seasonal influenza vaccine. [13][14][15] Compromised nutritional status [16][17][18] and decreased T-cell activity [18][19][20] could be contributing factors for that finding.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…vaccine being well tolerated and immunogenic (Nicholson et al, 2009), while other groups found that H1N1 split virus (detergent-disrupted virion) vaccine formulations containing alum were less immunogenic than formulations without adjuvant when given i.m. (Zhu et al, 2009). Chitosan has shown promising results in i.n.…”
Section: Introductionmentioning
confidence: 99%